Burden and Cost of Gastrointestinal, Liver, and Pancreatic Diseases in the United States: Update 2021 - Peery, Anne F; Crockett, Seth D; Murphy, Caitlin C; Jensen, Elizabeth T; Kim, Hannah P; Egberg, Matthew D; Lund, Jennifer L; Moon, Andrew M; Pate, Virginia; Barnes, Edward L; Schlusser, Courtney L; Baron, Todd H; et al. (Gastroenterology (New York, N.Y. 1943), 2022)
Gastrointestinal diseases account for considerable health care use and expenditures. We estimated the annual burden, costs, and research funding associated with gastrointestinal, liver, and pancreatic diseases in the United States. We generated estimates using data from the National Ambulatory Medical Care Survey; National Hospital Ambulatory Medical Care Survey; Nationwide Emergency Department Sample; National Inpatient Sample; Kids' Inpatient Database; Nationwide Readmissions Database; Surveillance, Epidemiology, and End Results program; National Vital Statistics System; Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research; MarketScan Commercial Claims and Encounters data; MarketScan Medicare Supplemental data; United Network for Organ Sharing registry; Medical Expenditure Panel Survey; and National Institutes of Health (NIH). Gastrointestinal health care expenditures totaled $119.6 billion in 2018. Annually, there were more than 36.8 million ambulatory visits for gastrointestinal symptoms and 43.4 million ambulatory visits with a primary gastrointestinal diagnosis. Hospitalizations for a principal gastrointestinal diagnosis accounted for more than 3.8 million admissions, with 403,699 readmissions. A total of 22.2 million gastrointestinal endoscopies were performed, and 284,844 new gastrointestinal cancers were diagnosed. Gastrointestinal diseases and cancers caused 255,407 deaths. The NIH supported $3.1 billion (7.5% of the NIH budget) for gastrointestinal research in 2020. Gastrointestinal diseases are responsible for millions of health care encounters and hundreds of thousands of deaths that annually costs billions of dollars in the United States. To reduce the high burden of gastrointestinal diseases, focused clinical and public health efforts, supported by additional research funding, are warranted.